EFFECTIVENESS OF THE SELECTED TOPICS IN SECONDARY SCHOOL MATHEMATICS TEXTBOOK WITH A REALISTIC APPROACH - Widdya Rahmalina; Suci Wulandari; Asrina Mulyati; Ria Finolia (Prima: Jurnal Pendidikan Matematika, 2026)
The Selected Topics in Secondary School Mathematics Textbook with a realistic approach is considered essential teaching material for Mathematics Education students at Adzkia University. This quantitative study utilized a One Group Pretest-Posttest design to assess the effectiveness of this textbook, using pretest and posttest data from 13 students. The methodologies applied include N-Gain analysis and the Wilcoxon Signed Rank test. The results of this study show a high effectiveness of the textbook, with an average N-Gain percentage of 81.15% and a significance value of 0.001 from the Wilcoxon test, indicating a significant difference in learning outcomes before and after using the textbook. These findings suggest that instructors of other courses should also consider developing textbooks that use a realistic approach.